Mesoporous Fe2O3-TiO2 integrated with plasmonic Ag nanoparticles for enhanced solar H2 production - Mani, Sunesh S.; Rajendran, Sivaraj; Saju, Simi; Babu, Bindhya M.; Mathew, Thomas; Gopinath, Chinnakonda S. (Chemistry-An Asian Journal, 2025)
Present work describes a sol-gel assisted one-pot synthesis of mesoporous Fe2O3-TiO2 nanocomposites (TiFe) with different Ti : Fe ratios, and fabrication of Ag-integrated with TiFe nanocomposites (TiFeAg) by a chemical reduction method and demonstrated for high solar H2 generation activity in direct sunlight. Enhanced solar H2 production is attributed to the light absorption from entire UV+Visible region of solar spectrum combined with Schottky (Ag-semiconductor) and heterojunctions (TiO2-Fe2O3), as evidenced from HRTEM and various characterization studies. TiFeAg-2 thin film (1 wt % Ag-loaded TiFe-4) displayed the highest activity with a solar H2 yield of 7.64 mmol h-1g-1, which is 48 times higher than that of bare TiO2 and 5 times higher in thin film form compared to its powder counterpart. Schottky and heterojunctions formed at the interface efficiently separate the charge carriers and increase the hydrogen production activity. The highest H2 production activity of TiFeAg-2 is partly attributed to the heterogeneous distribution of Fe3+ and metallic Ag-species with relatively high Ag/Ti surface atomic ratio. A plausible photocatalytic reaction mechanism on TiFeAg nanocomposite may involve the direct electron transfer from both Fe2O3 and TiO2 to Ag nanoparticles which are subsequently utilized for the reduction of H+ to H2.
Keywords: energy conversion; green hydrogen; Photocatalysis; Solar harvesting; water splitting